Efficacy of jianpi huatan granule in reducing colorectal cancer metastasis and recurrence after radical resection and adjuvant chemotherapy: Study protocol for a randomised, double-blind, placebo-controlled, multicentre trial - Li, Liusheng; Qu, Qian; Cui, Ning; Cai, Linlin; Zou, Jianhua; Wu, Jiao; Hao, Tengteng; Wu, Yu (Frontiers in Pharmacology, 2022)
Background: The high incidence and mortality rates of colorectal cancer (CRC) are a severe challenge in China. In patients with stage III and high-risk stage II CRC after radical resection and postoperative adjuvant chemoradiotherapy, 40–60% experience recurrence and metastasis. Several years of clinical practice have shown that traditional Chinese medicine, including Jianpi Huatan granule (JHG), effectively prevents stage III and high-risk stage II CRC recurrence and metastasis after radical resection and postoperative standard adjuvant chemotherapy. However, high-level systematic plans and evidence-based medicine are lacking in this regard. Therefore, this randomised control trial aimes to determine the efficacy of JHG in reducing stage III and high-risk stage II CRC metastasis and recurrence after radical resection and postoperative standard adjuvant chemotherapy. Methods: This is a multicentre, randomised, double-blind, placebo-controlled clinical trial. Three hundred and fifty patients with stage III or high-risk stage II CRC who completed adjuvant chemotherapy after radical resection will be recruited from eight medical centres in China and randomly assigned to test (n=175) and control (n=175) groups at a ratio of 1:1. The test group will receive oral JHG for three months, whereas the control group will receive oral placebo for three months. The primary outcomes will be the disease-free survival and 1-, 2-, and 3-year metastasis and recurrence rates, whereas the secondary outcomes will be quality of life and circulating tumour cells. The patients will be followed-up monthly during treatment and every 3–6 months thereafter until recurrence, metastasis, death, or the end of the study. Trial registration: This trial was registered at ClinicalTrials.gov (NCT03716063).